Analysis on effect of nanofluid on process parameters in machining of EN19 steel. (31st October 2022) - N, Sateesh; Subbiah, Ram; Nookaraju, BCh; Lakshmi, A. Anitha; P, Prashanth kumar
ABSTRACT: Machining is the most fundamental process in manufacturing industry. The heat generated on the working surface of the tool during machining is critical to determining the dimensional accuracy and surface quality of the workpiece. Conventional cutting fluids are hazardous to the health of workers and cause environmental pollution. This paper focuses on the effect of vegetable oil-based nanofluid on the machining performance in turning of EN19 steel through Minimum Quantity Lubrication (MQL). Canola oil is used as a base lubricant with various inclusions of boric acid powder nanoparticles. Machining parameters such as tool temperature and cutting forces are measured during machining. After processing, the surface roughness of the part is measured. The change in the temperature of the cutting tool and the roughness of the processed surface, depending on the cutting speed and feed, is studied at various percentages of suspensions of nano boric acid in canola oil. From the results of analysis it is found that cutting force, tool temperature and surface roughness decreased with increasing percentage of boric acid nanoparticles.